Nature conservation in Japan - Korponai, Gábor (JOURNAL OF LANDSCAPE ECOLOGY, 2012)
The history of the Japanese nature conservation has started about 100 years ago. As a result, the natural park system provides three different categories of natural parks: national parks, quasi-national parks and prefectural natural parks. As Japan is a small island country with one of the highest population densities in the world with a long history of private land ownership, it is next to impossible to set aside large park areas specifically for the purpose of protection. To feed the nation, the first priority of land use has been farming and other primary industries. Because of these reasons, the Japanese government had to create natural parks not necessarily where it owned land but where it recognized the need to preserve nature. It is characteristic of Japanese natural parks that various land owners cooperatively maintain the landscape of a park. This paper is trying to present the system of nature conservation and landscape preservation of the secondary nature, the so called ’Satoyama’ and the cooperation among the state, local governments, NGO-s, landowners and other stakeholders.
Keywords: nature conservation; Japan; Satoyama; natural park categories; zoning system